Self-efficacy and embodiment associated with Alexander Technique lessons or with acupuncture sessions: A longitudinal qualitative sub-study within the ATLAS trial - Wenham, Aniela (Complement Ther Clin Pract, 2018)
BACKGROUND AND PURPOSE: A large randomised controlled trial found that the provision of either Alexander Technique lessons or acupuncture, for those with chronic neck pain, resulted in significantly increased self-efficacy when compared with usual care alone. In turn, enhanced self-efficacy was associated with significant reductions in neck pain at 6 and 12 months. In this analysis we explore the perspectives of participants within the trial, with the aim of gaining a better understanding of how these interventions had an impact. METHODS: We used a longitudinal qualitative approach; in-depth interviews, informed by a topic guide, were conducted with a sample of the trial population. Participants were interviewed twice: at around six months (n = 30) and twelve months (n = 26) after trial entry. Analysis was guided by the principles of grounded theory, and key themes were developed. RESULTS: Five key themes emerged: pre-trial experiences of biomedical treatment against which subsequent interventions were compared; emergence of tangible benefits from the interventions; factors that contributed to the observed benefits, notably growing self-care and self-efficacy; a developing sense of embodiment as an integral part of the transformative process; and contribution of these factors to sustaining benefits over the longer term. CONCLUSIONS: In-depth interviews revealed a rich array of experiences. They gave insight into the positive impact of the interventions on development of self-care, self-efficacy and embodiment. These findings complement the quantitative trial data, providing a more nuanced understanding of the factors that underpin the previously quantified improvement in self-efficacy and its association with longer-term reductions in pain.